Exiting primary care providers - Katrin Zocher (ZBW - Leibniz Information Centre for Economics, 2022)
This article studies the impact of primary care providers (PCPs) exit from the local health care system on patients' health care utilization. I compare patients with each other whose physicians have left the local health care system at different points in time due to retirement, relocation, or other reasons. Estimation results indicate that the imminent exit leads soon-leaving physicians to changing their treatment behavior, which has a significant impact on patients' health care spending. In addition, successors and new PCPs provide significantly more preventive services in the post-exit-period and refer patients more often to specialists for further examinations than the physicians who exit later. The increased inpatient expenditures in the post-exit period are caused by patients themselves (through outpatient department visits), by the new PCPs (through referrals), and presumably by specialists. Self-initiated substitution behavior of patients (e.g., less PCP care, more specialist care) after the exit is observed but is low in magnitude. Although an overall increase in health service utilization is observed, mortality in the post-exit periods is significantly increased among affected patients. A possible explanation is the low frequency follow-up care of patients who were referred to hospitals by their former PCP in the notification-period.
Keywords: I11; I12; I18; 330; physicians exit; retirement; disruption; discontinuity; successor